Asymmetric S=N-embedded polyaromatic construction via enantioselective Pd-catalyzed C–H activation - Daming Zeng; Xinyu Zhang; Ming Wang; Xuefeng Jiang (Nature Communications)
Abstract Heteroatom-doped polyaromatic hydrocarbons show great potential for advancing photoelectric materials. SVI=N doping, characterized by soft-hard atom binding, donor-acceptor transmission, and chiroptical tuning, provides a powerful approach for further optimizing the performance and functionality of these materials. However, the introduction of chiral sulfur(VI) has been a formidable challenge due to the intricate enantioselective discrimination and embedded linkages with the heteroatoms in the polyaromatic systems. Herein, we establish an enantioselective Pd-catalyzed desymmetrization of diaryl sulfoximines and sulfondiimines to access the chiral SVI=N-doped heterocycles with high yields and enantioselectivities. The flexibility and rigidity of the molecule has a distinct effect on the enantioselectivity. The split aromatic compounds exhibit C–H···π interactions involving the additive TMCPA with the ligand and the S-aryl motif, producing the (R)-configuration, while combined aromatic compounds exhibit the opposite (S)-configuration due to the restricted bond rotation. The photophysical and chiroptical study demonstrates an SVI=N-doped carbazole-based polyaromatic heterocycle with intense double absorption peaks and a favorable luminescence dissymmetry factor.